The economic impact of alcohol consumption: a systematic review - Lertpitakpong Chanida; Yothasamut Jomkwan; Teerawattananon Yot; Thavorncharoensap Montarat; Chaikledkaew Usa (BMC, 2009)
Abstract Background Information on the economic impact of alcohol consumption can provide important evidence in supporting policies to reduce its associated harm. To date, several studies on the economic costs of alcohol consumption have been conducted worldwide. This study aims to review the economic impact of alcohol worldwide, summarizing the state of knowledge with regard to two elements: (1) cost components included in the estimation; (2) the methodologies employed in works conducted to date. Methods Relevant publications concerning the societal cost of alcohol consumption published during the years 1990-2007 were identified through MEDLINE. The World Health Organization's global status report on alcohol, bibliographies and expert communications were also used to identify additional relevant studies. Results Twenty studies met the inclusion criteria for full review while an additional two studies were considered for partial review. Most studies employed the human capital approach and estimated the gross cost of alcohol consumption. Both direct and indirect costs were taken into account in all studies while intangible costs were incorporated in only a few studies. The economic burden of alcohol in the 12 selected countries was estimated to equate to 0.45 - 5.44% of Gross Domestic Product (GDP). Conclusion Discrepancies in the estimation method and cost components included in the analyses limit a direct comparison across studies. The findings, however, consistently confirmed that the economic burden of alcohol on society is substantial. Given the importance of this issue and the limitation in generalizing the findings across different settings, further well-designed research studies are warranted in specific countries to support the formulation of alcohol-related policies.